Artificial Intelligence Workshop: Introducing AI Concepts Using Neural Style Transfer - Anh Tang; Anca Doloc-Mihu (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
With the exponential growth of Artificial Intelligence (AI) technologies in recent years, it is more important than ever to increase AI literacy for our students at multiple grade levels, including college students and K-12 students. AI is a broad and complex topic that requires a steep learning curve for most students. This research project focuses on determining the best way to introduce AI to students with little to no prior experience in AI within the scope of a one-hour workshop setting, while still making sure they are having fun exploring this new technology.